2013
DOI: 10.1371/journal.pone.0074164
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ventral Striatal Volume in College-Aged Binge Drinkers

Abstract: BackgroundBinge drinking is a serious public health issue associated with cognitive, physiological, and anatomical differences from healthy individuals. No studies, however, have reported subcortical grey matter differences in this population. To address this, we compared the grey matter volumes of college-age binge drinkers and healthy controls, focusing on the ventral striatum, hippocampus and amygdala.MethodT1-weighted images of 19 binge drinkers and 19 healthy volunteers were analyzed using voxel-based mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 45 publications
11
63
2
1
Order By: Relevance
“…In support of the current results, a recent study in heavy drinking young adults showed larger ventral striatum volume in users compared with controls (Howell et al, 2013). The authors of this study suggested that the fi ndings, opposite to what has been reported in alcoholics, could represent a phenotypic risk factor for more severe alcohol-related problems.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In support of the current results, a recent study in heavy drinking young adults showed larger ventral striatum volume in users compared with controls (Howell et al, 2013). The authors of this study suggested that the fi ndings, opposite to what has been reported in alcoholics, could represent a phenotypic risk factor for more severe alcohol-related problems.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, studies have reported gray matter (GM) brain volumetric abnormalities in subcortical regions that encompass reward-related or limbic areas in adult alcoholics (Agartz et al, 1999;Durazzo et al, 2011;Le Berre et al, 2014;Makris et al, 2008;Ozsoy et al, 2013;Sullivan et al, 2005;Wrase et al, 2008), adolescent and young adult heavy drinkers (Howell et al, 2013;Squeglia et al, 2014), and alcohol-dependent youth (De Bellis et al, 2000Nagel et al, 2005). It is possible that some of these subcortical abnormalities could have been present before the onset of heavy alcohol use and may have increased the risk for alcohol dependence.…”
mentioning
confidence: 99%
“…[2013] [102] Howell, NA et al PLoS One 19 binge drinkers and 19 healthy volunteers were analyzed using voxelbased morphometry. Participants were included if they were greater than 18 years old, had no history of regular or current use of other substances, and were free from any major psychiatric disorders.…”
Section: Alcohol Clinmentioning
confidence: 99%
“…There are numerous researches studying individuals throughout the life span that have shown hippocampal anomalies associated with alcohol consumption [102]. Results from a recent longitudinal brain imaging study of male P rats (from P88 to 578) have revealed that free-choice ethanol consumption attenuated the growth and expansion of brain structures, including the corpus callosum and hippocampus [103].…”
Section: The Physiological Effects Of Alcohol Abusementioning
confidence: 99%
“…Sobre la base de los resultados observados en las mujeres BDs, los autores propusieron que el consumo intensivo de alcohol durante la adolescencia estaba asociado con un retraso en el neurodesarrollo y, por lo tanto, con un mayor espesor cortical. En consonancia con estos resultados, un estudio reciente, procedente de otro grupo de investigaciĂłn, ha observado mayor volumen de sustancia gris en el estriado ventral o nĂșcleo accumbens (NAcc) en los jĂłvenes BDs que en los controles, lo que, segĂșn los autores, es indicativo de una relativa inmadurez neuroestructural en la poblaciĂłn BD (Howell et al, 2013).…”
Section: AnomalĂ­as De Tipo Estructural Y Funcional Ligadas Al PatrĂłn unclassified